A (des)educação dos educadores: repensando a relação teoria/prática dentro da própria escola - Butler, Sheila Perla Mandel (1985)
Considering that educational practice is intimately related to the social relationships in society, it is implied that education cannot be seen as a problem in itself but as an integral part of social reality even though a contradictory part which mediates between opposite interests. From this standpoint, this study proposes to reflect on the professional preparation of teachers and, more specifically the educational practice of the teacher, its conditioning and contradictions. In order to investigate the problems and incongruities which are present in the professional preparation and the educational practice of teachers, the results of two projects were analysed; one involved the Centre of Educational Studies of the University of Santa Ursula (USU) and the other the "Projeto MEC/USU" which, in two sub-projects, involved the university and schools offering adult education and primary schools of the city of Rio de Janeiro, Brazil. From these results it was possible to discover that the function which the professional training of teachers has been performing, is one of DIS-EDUCATION, one of the key but contradictory aspects of this being the relationship between theory and practice. It is proposed that it is necessary to rethink this contradictory relationship within the school. It is suggested that the professional preparation of teachers needs to provide the fundamental tools for the teacher to establish the connection between his educational practice and society as a whole. In this way, it is possible to see the school as a 'space' where the teacher at the very least should understand the particularity of education in today's society and the real possibilities of his educational practice, looking at it with a view to transforming it.